The Use of Microorganisms for Gene Transfer and Crop Improvement - Baloglu, Mehmet C.; Kavas, Musa; Gurel, Songul; Gurel, Ekrem (Elsevier BV, 2018)
Kavas, Musa/0000-0001-5903-2873; Gurel, Ekrem/0000-0001-6262-2866

WOS: 000463411400001

…
Keywords: 2. Zero hunger; 15. Life on land